2007
DOI: 10.1093/cercor/bhm068
|View full text |Cite
|
Sign up to set email alerts
|

Specificity in Inhibitory Systems Associated with Prefrontal Pathways to Temporal Cortex in Primates

Abstract: The prefrontal cortex selects relevant signals and suppresses irrelevant stimuli for a given task through mechanisms that are not understood. We addressed this issue using as a model system the pathways from the functionally distinct prefrontal areas 10 and 32 to auditory association cortex, and investigated their relationship to inhibitory neurons labeled for calbindin (CB) or parvalbumin (PV), which differ in mode of inhibition. Projection neurons in area 10 originated mostly in layers 2-3 and were interming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
111
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(125 citation statements)
references
References 102 publications
13
111
1
Order By: Relevance
“…Our results suggest that BSI can serve as a top-down control mechanism to rapidly and parametrically modulate a perceptual decision. This finding suggests a specific functional role of long-distance top-down projection onto GABAergic inhibitory neurons, which has recently been documented for pathways from the prefrontal cortex to other parts of the brain (Barbas et al 2005;Bunce and Barbas 2011;Medalla et al 2007). …”
supporting
confidence: 63%
See 1 more Smart Citation
“…Our results suggest that BSI can serve as a top-down control mechanism to rapidly and parametrically modulate a perceptual decision. This finding suggests a specific functional role of long-distance top-down projection onto GABAergic inhibitory neurons, which has recently been documented for pathways from the prefrontal cortex to other parts of the brain (Barbas et al 2005;Bunce and Barbas 2011;Medalla et al 2007). …”
supporting
confidence: 63%
“…Indeed, various studies have suggested that the prefrontal cortex plays a critical role in top-down executive control (Asplund et al 2010;Isoda and Hikosaka 2007;Miller and Cohen 2001;Ridderinkhof 2004;Tomita et al 1999). Long-range excitatory projections from the prefrontal cortex to posterior cortical areas target both pyramidal cells and inhibitory interneurons (Barbas et al 2005;Bunce and Barbas 2011;Medalla et al 2007). The recipient inhibitory neurons could in turn target pyramidal cells and thus instantiate the inhibitory part of a top-down BSI (Vogels and Abbott 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Together, our results indicate that category selectivity is higher in putative pyramidal cells, but discriminability is more reliable in putative interneurons. We speculate that reliability is more important for extraction and sharpening numerosity representations within the local PFC microcircuitry, whereas selectivity may play a more prominent role in downstream decisionrelated processing (Medalla et al, 2007).…”
Section: Coding Selectivity Versus Coding Reliabilitymentioning
confidence: 95%
“…This function is related with so-called "inhibitory control" of behavior (Miller & Wang, 2006). Clinical evidence (e.g., Luria, 1969;Stuss & Knight, 2002) and experimental research (e.g., Leung & Cai, 2007;Medalla, Lera, Feinberg, & Barbas, 2007) suggest that the neural substrate for this inhibitory function resides mainly in the medial and orbital portions of the prefrontal cortex.…”
Section: Emotional/motivational Executive Functionsmentioning
confidence: 99%